Progression of acute hydrocephalus in subarachnoid haemorrhage: a case report documented by serial CT scanning. - Rinkel, G J (1990)
A patient with a perimesencephalic subarachnoid haemorrhage gradually developed, within the first day, progressively impaired consciousness, small non-reactive pupils, and defective upward gaze. Three successive CT scans showed progressive enlargement of the lateral and third ventricles. Ventricular shunting resulted in complete recovery.